Nanometer polishing process for surface of titanium heating disc
By electrochemical polishing using a polishing liquid containing ammonium sulfate, sodium citrate, glucose and citric acid on the surface of the titanium heating disk, the problem that it is difficult to achieve mirror effect on the surface of the titanium heating disk is solved, and an efficient polishing and a safe production environment are achieved.
Patent Information
- Application Number
- CN202510048082.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-13
AI Technical Summary
In the prior art, the surface of the titanium heating disk is difficult to achieve mirror effect, and the polishing efficiency is low, and there is a risk of fire.
A titanium heating disk surface nanopolishing process is adopted, and electrochemical polishing is performed using a polishing liquid containing ammonium sulfate, sodium citrate, glucose and citric acid. The temperature, voltage and time of the polishing liquid are controlled, and the step of washing and blow-drying of nitrogen is combined.
It realizes efficient polishing of the surface of the titanium heating disk, achieves mirror effect, improves finish and flatness, reduces the risk of fire, and improves the safety of the operating environment.
Smart Images

Figure BDA0005239132790000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polishing, and in particular to a nano-polishing process for the surface of a titanium heating plate. Background Art
[0002] Polishing is the process of processing the surface of a workpiece to make it highly smooth. Through polishing, the tiny bumps on the surface can be eliminated, making it highly smooth and enhancing the light reflection effect, thereby improving the appearance and performance of the product.
[0003] There are many polishing methods, including mechanical polishing, chemical polishing, electrolytic polishing, ultrasonic polishing and fluid polishing. At present, due to the hard surface of the titanium heating plate, it is difficult to remove the surface oxide layer by general physical polishing. Imported hard sandpaper is usually used for polishing, but the sandpaper polishing efficiency is low, the sparks are very large, and there is a great risk of fire during the production process.
[0004] Electrochemical polishing is a processing method based on the principle of electrochemical dissolution of metal anodes to gradually make the metal surface microscopically flat, so that the surface of the titanium heating plate can achieve a mirror effect and significantly improve the surface finish. The polishing process is relatively simple, and it is easy to control the polishing thickness and polishing speed. The finish and flatness after polishing are better than mechanical polishing.
[0005] The prior art discloses a titanium alloy polishing liquid containing perchloric acid, sodium perchlorate, lactic acid, and anhydrous ethanol. When the polishing liquid is used for polishing, a high-hardness oxide film is easily generated on the surface of the titanium alloy substrate, which increases the difficulty of polishing. During the polishing process, polishing lines are easily generated on the surface of the titanium alloy, making it difficult to achieve a mirror effect. Summary of the invention
[0006] In order to improve the problem that polishing lines are easily generated on the surface of a titanium alloy substrate after being treated with a polishing liquid, and it is difficult to achieve a mirror effect, the present application provides a nano-polishing process for the surface of a titanium heating plate.
[0007] The present application provides a titanium heating plate surface nano-polishing process, which adopts the following technical solutions: A titanium heating plate surface nano-polishing process comprises the following steps: placing a workpiece in a polishing liquid, the temperature of the polishing liquid is 50-55°C, electrochemical polishing is performed at a constant voltage, the voltage is controlled at 20-30V, the power-on time is 5-10min, after the electrochemical polishing is completed, the workpiece is taken out, washed with water, and dried with nitrogen; The polishing liquid comprises polishing salt and deionized water, wherein the polishing salt comprises the following components in percentage by mass: 30-40% ammonium sulfate, 28-32% sodium citrate, 7-13% glucose and 22-28% citric acid.
[0008] By adopting the above technical solution, in the polishing liquid, ammonium sulfate mainly plays the role of improving the working environment and improving the escape of nitrogen oxides during polishing, thereby reducing the health hazards to operators. Sodium citrate has good complexing ability and buffering properties, which helps to stabilize the pH value of the polishing liquid in the polishing liquid and prevent the polishing effect from being affected by changes in pH value during the polishing process. Sodium citrate can also be used as a chelating agent to remove metal ion impurities on the surface of the workpiece and further improve the polishing quality. Glucose plays the role of auxiliary polishing in the polishing liquid, and the addition of glucose helps to obtain a smoother and more uniform polished surface. In addition, glucose also affects the polishing effect by increasing the viscosity of the polishing liquid or improving the dispersibility of the polishing particles.
[0009] Citric acid is an organic acid with excellent complexing ability and chelating properties. In the polishing liquid, citric acid can remove oxides and impurities on the surface of the workpiece and promote the polishing reaction. Citric acid can also adjust the pH value of the polishing liquid to keep it within an appropriate range, thereby ensuring the stability of the polishing effect. In addition, citric acid can also be used as a reducing agent to participate in the redox reaction during the polishing process, which helps to obtain a brighter polished surface. When ammonium sulfate, sodium citrate, glucose and citric acid are mixed as a polishing liquid for titanium heating plates, they each play different roles and jointly achieve an efficient polishing effect.
[0010] Set the polishing liquid temperature, polishing voltage and polishing time to ensure uniform polishing, rinse with running water to ensure that the workpiece surface is clean, use nitrogen to blow dry the workpiece to avoid residual water stains, ensure that nitrogen blows evenly to avoid local over-dryness or over-wetness.
[0011] Preferably, the polishing salt comprises the following components in the following mass percentages: 35% ammonium sulfate, 30% sodium citrate, 10% glucose and 25% citric acid.
[0012] By adopting the above technical solution, the amount of each component of the polishing salt is further limited, and the obtained polishing liquid has a good comprehensive effect. The components are mixed according to the above proportions to ensure the consistency and stability of the polishing effect. Through precise component ratios and strict operating conditions, efficient polishing of the workpiece surface can be achieved. Ammonium sulfate has good electrochemical properties and polishing effects, which helps to adjust the pH value of the polishing liquid and stabilize the polishing process. In addition, ammonium sulfate also has a positive effect on the surface quality of the polished workpiece, such as improving gloss and flatness.
[0013] Sodium citrate can form a stable complex with metal ions, which helps to remove metal oxides and impurities on the surface of the workpiece. It can also adjust the pH value of the polishing liquid to ensure the stability of the polishing effect. Glucose helps to improve the viscosity or dispersibility of the polishing liquid to affect the polishing effect and obtain a smoother and more uniform polished surface. Citric acid has excellent complexing ability and chelating properties, which can remove oxides and impurities on the surface of the workpiece, promote the polishing reaction, and work synergistically with ammonium sulfate to jointly adjust the pH value and electrochemical properties of the polishing liquid.
[0014] Preferably, the workpiece is pretreated before being placed in the polishing liquid, comprising the following steps: soaking the workpiece in an acid solution for 30-35 minutes, then washing with water, then ultrasonically cleaning the workpiece in a cleaning liquid for 1-2 hours, washing with ethanol, and drying to obtain a pretreated workpiece; The cleaning solution comprises the following components: sodium hydroxide, sodium gluconate, sodium borate, sodium ethylenediaminetetraacetate, modified xanthan gum, octylphenol polyoxyethylene ether, modified acrylic resin, triethanolamine oleic acid soap, polydimethylsilane and deionized water.
[0015] By adopting the above technical solution, the workpiece is immersed in an acid solution to remove the oxide layer, rust or other metal contaminants on the surface of the workpiece. The workpiece is then placed in a cleaning solution and cleaned using ultrasound, which uses tiny bubbles generated by high-frequency sound waves to impact and peel off dirt and residues on the surface of the workpiece. The workpiece is further cleaned with ethanol to remove grease, grease residues and other organic contaminants that cannot be completely removed by water, thereby obtaining a pre-treated workpiece.
[0016] In the cleaning solution, sodium hydroxide can remove grease, dirt and oxide layers on the surface of the titanium heating plate, improving the cleanliness of the surface. Sodium gluconate has excellent chelating effect and can form stable complexes with metal ions to remove metal ions and other impurities on the surface of the titanium heating plate. It also has a certain corrosion inhibition effect to protect the titanium material from corrosion. Sodium borate plays a buffering role in the cleaning solution, stabilizes the pH value of the cleaning solution, removes stains on the surface of the titanium heating plate, and improves the cleaning effect. Sodium ethylenediaminetetraacetic acid has a strong chelating ability and can form stable complexes with metal ions to remove metal oxides and other corrosion products on the surface to prevent re-corrosion.
[0017] Modified xanthan gum is present in the cleaning liquid as a thickener, which adjusts the adhesion of the system, helps to remove impurities on the surface of the titanium heating plate, and can also maintain the stability of the cleaning liquid and improve the cleaning effect. Octylphenol polyoxyethylene ether has excellent emulsification and dispersion ability, can quickly form a stable emulsion, and has a good emulsification and dispersion effect on grease, oil, etc., thereby effectively removing oil and impurities on the surface of the titanium heating plate. Modified acrylic resin is used to improve the wettability and adhesion of the cleaning liquid, which helps the cleaning agent to better penetrate into the tiny depressions and gaps on the surface of the titanium heating plate, thereby improving the cleaning effect.
[0018] Triethanolamine oleic acid soap has excellent emulsifying and dispersing ability and anti-rust performance, removes grease, oil and other impurities on the surface, and forms a protective film on the metal surface to prevent corrosion and oxidation. Polydimethylsilane has a high degree of chemical stability and inertness, plays a lubricating and dispersing role, helps the cleaning agent to better penetrate the surface of the titanium heating plate and improve the cleaning efficiency. The various components in the cleaning solution work together on the surface of the titanium heating plate to improve the cleanliness and glossiness of the surface by removing grease, dirt, oxides and other impurities. At the same time, the various components also work synergistically with each other to maintain the stability and effect of the cleaning solution.
[0019] Preferably, the cleaning solution comprises the following components in parts by weight: 6-9 parts of sodium hydroxide, 30-35 parts of sodium gluconate, 3-5 parts of sodium borate, 15-18 parts of sodium ethylenediaminetetraacetate, 3-5 parts of modified xanthan gum, 5-8 parts of octylphenol polyoxyethylene ether, 6-8 parts of modified acrylic resin, 2-5 parts of triethanolamine oleic acid soap, 1-3 parts of polydimethylsilane, and 350-380 parts of deionized water.
[0020] By adopting the above technical scheme, the dosage range of each component in the cleaning solution is further limited, and the components cooperate with each other, so that the cleaning solution obtained has a better cleaning effect. Sodium hydroxide can effectively remove grease, dirt and mild oxide layers on the surface of the titanium heating plate, increase the pH value of the cleaning solution, and help other active ingredients to play a role. Sodium gluconate forms a stable complex with metal ions to prevent the ions from redepositing on the surface of the titanium heating plate during the cleaning process, enhance the cleaning effect, and make dirt easier to rinse off. Sodium borate stabilizes the pH value of the cleaning solution to prevent the cleaning effect from being affected by pH fluctuations. Sodium ethylenediaminetetraacetic acid further ensures that metal ions will not redeposit on the surface of the titanium heating plate, which helps to remove oxides and other impurities that are difficult to clean.
[0021] Modified xanthan gum increases the viscosity of the cleaning solution, making it easier to apply and adhere to the surface of the titanium heating plate, preventing the cleaning solution from stratifying or settling during use. Octylphenol polyoxyethylene ether has excellent emulsification and dispersion capabilities, emulsifying pollutants such as grease and oil into tiny particles, dispersing them in the cleaning solution for easy rinsing. Modified acrylic resin improves the uniformity and thoroughness of cleaning, improves the wettability and adhesion of the cleaning solution, and ensures that the cleaning agent can better penetrate into the tiny depressions and gaps on the surface of the titanium heating plate. Triethanolamine oleic acid soap has excellent emulsification and dispersion capabilities and anti-rust properties, forming a protective layer during the cleaning process to prevent the surface of the titanium heating plate from corrosion and oxidation.
[0022] Polydimethylsiloxane improves the dispersibility and permeability of the cleaning agent on the surface, accelerates the cleaning process, changes the energy state of the titanium heating plate surface, and makes it easier to separate the dirt from the surface. Through the synergistic effect of various components, the cleaning liquid can effectively remove grease, dirt, oxides and other impurities on the surface of the titanium heating plate, while protecting the titanium material from corrosion and oxidation.
[0023] Preferably, the preparation method of the modified xanthan gum comprises the following steps: dispersing the xanthan gum in deionized water, stirring at 70-75°C for 1-2h, adding potassium hydroxide, adjusting the pH value to 10-11, then adding polysorbate and saccharin, stirring at 80-85°C for 50-55min, filtering, washing with anhydrous ethanol, and drying to obtain the modified xanthan gum.
[0024] By adopting the above technical solution, the xanthan gum is dispersed in deionized water, which helps to reduce the agglomeration phenomenon during subsequent stirring, ensures that the xanthan gum is fully dissolved and forms a uniform aqueous solution. Adjusting the pH value of the solution to 10-11 helps the dispersion and dissolution of the xanthan gum in water, and improves the solubility and dispersibility of the xanthan gum.
[0025] Polysorbate and saccharin are added. Polysorbate has good emulsification, dispersing and solubilizing effects, further reducing the surface tension of the system, making xanthan gum molecules more easily dispersed in water, thereby improving its solubility and dispersibility. Saccharin not only promotes the dissolution of xanthan gum, but also increases the viscosity and consistency of xanthan gum, and can form a tighter network structure with xanthan gum, thereby increasing the viscosity of the system.
[0026] The modified xanthan gum is subsequently used in the cleaning of titanium heating plates, which not only increases the viscosity of the liquid, helps the cleaning liquid to better adhere to the surface of the titanium heating plate and improves the cleaning effect; but also the stability of the modified xanthan gum can prevent the cleaning liquid from stratifying or precipitating during use, ensuring the uniformity and stability of the cleaning liquid.
[0027] Preferably, the mass ratio of xanthan gum, polysorbate and saccharin is 1:0.1-0.3:0.6-0.8.
[0028] By adopting the above technical scheme, the mass ratio of xanthan gum, polysorbate and saccharin is further limited within a certain range, and the obtained xanthan gum has excellent dispersibility and viscosity. Polysorbate has excellent wetting, dispersing and emulsifying properties, can stabilize the colloidal structure in the xanthan gum alkaline solution, and prevent the aggregation and precipitation of colloidal particles. Saccharin can form a tighter network structure with xanthan gum, thereby increasing the viscosity of the system. There is a synergistic effect between xanthan gum, polysorbate and saccharin, which is subsequently applied to the surface cleaning of titanium heating plate. The wetting and dispersing effect of polysorbate is combined with the suspension effect of xanthan gum, which can more effectively remove the stains and dirt on the surface of titanium heating plate. The stabilizing effect of xanthan gum and the viscosity regulating effect of saccharin can ensure that the cleaning agent maintains stable performance during use, while increasing its adhesion and cleaning effect.
[0029] Preferably, the preparation method of the modified acrylic resin comprises the following steps: dispersing methyl methacrylate in deionized water, stirring at a temperature of 60-65°C for 1-2h, adding cellulose nanocrystals and sodium dodecylbenzene sulfonate, stirring at a temperature of 120-130°C for 2-3h, drying, and grinding to obtain the modified acrylic resin.
[0030] By adopting the above technical scheme, methyl methacrylate is dispersed in deionized water and stirred thoroughly to ensure its uniform dispersion. Cellulose nanocrystals and sodium dodecylbenzene sulfonate are added. Cellulose nanocrystals can provide additional structural strength and stability, while sodium dodecylbenzene sulfonate acts as a surfactant to help improve the wettability and dispersibility of the mixture. Cellulose nanocrystals and sodium dodecylbenzene sulfonate can be better integrated into the methyl methacrylate network and cross-linked into a network structure. The modified acrylic resin obtained has good mechanical properties, adhesion, weather resistance and stability.
[0031] In the subsequent application of cleaning the surface of titanium heating plates, the modified acrylic resin can increase the viscosity of the cleaning agent, allowing it to form a more durable coating on the surface of the titanium heating plate, thereby improving the cleaning efficiency. The modified acrylic resin has good weather resistance and stability, and can maintain stable cleaning performance under various environmental conditions. The modified acrylic resin cleaning agent can effectively remove various stains and dirt on the surface of the titanium heating plate, including grease, dust, oxides, etc., and can form a protective film to prevent the surface of the titanium heating plate from further corrosion and damage.
[0032] Preferably, the mass ratio of the methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate is 1:0.4-0.5:0.1-0.2.
[0033] By adopting the above technical solution, the mass ratio of methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate is further limited within a certain range, and the obtained modified methyl methacrylate has better comprehensive performance, and is subsequently applied to the surface cleaning of titanium heating plates, and has better cleaning effect. The mixture of methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate has a synergistic effect. Methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate can form a cross-linked network structure, which improves the mechanical properties, weather resistance, adhesion and stability of acrylic resin.
[0034] Modified methyl methacrylate helps dissolve grease stains on the surface of the titanium heating plate, increases the viscosity and stability of the cleaning solution, thereby improving the cleaning effect. It can also form a protective film on the surface of the titanium heating plate to prevent excessive corrosion or damage to the surface by the cleaning agent. Methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate work together in the mixture to play a cleaning role. Their combination not only improves the cleaning efficiency, but also reduces the risk of damage to the surface of the titanium heating plate.
[0035] Preferably, the acid solution is sulfuric acid, hydrofluoric acid, and deionized water in a mass ratio of 30-35:6-9:100.
[0036] By adopting the above technical solution, the components of the acid solution and the mass ratio between the components are further limited, and the obtained cleaning effect on the surface of the titanium heating plate is better. Sulfuric acid, hydrofluoric acid and deionized water cooperate with each other in the cleaning process and play a cleaning role together. Sulfuric acid and hydrofluoric acid are responsible for chemical reaction to remove stains, while deionized water is responsible for dilution and flushing. Sulfuric acid can react chemically with oxides, dirt, etc. on the surface of the titanium heating plate to generate soluble sulfates, thereby removing them. Sulfuric acid can also increase the acidity of the solution, which helps to enhance the cleaning effect of hydrofluoric acid.
[0037] Hydrofluoric acid removes stubborn stains and oxide layers on the surface of the titanium heating plate. In combination with sulfuric acid, hydrofluoric acid can penetrate deeper into the stains, accelerating their decomposition and removal. Deionized water is used as a solvent to dilute sulfuric acid and hydrofluoric acid to a moderate concentration, which ensures the cleaning effect and avoids excessive corrosion. The acid solution can effectively remove stains, oxide layers and other impurities on the surface of the titanium heating plate, restoring its smoothness and thermal conductivity.
[0038] Preferably, the method for preparing the polishing liquid comprises the following steps: uniformly mixing ammonium sulfate, sodium citrate, glucose and citric acid, dispersing the mixture in deionized water, and stirring for 2-3 hours to obtain the polishing liquid.
[0039] By adopting the above technical solution, the raw materials are mixed evenly, and the polishing liquid obtained has better stability and polishing performance, which is conducive to the subsequent electrochemical polishing.
[0040] In summary, this application has the following beneficial effects: 1. In this application, when ammonium sulfate, sodium citrate, glucose and citric acid are mixed as a polishing liquid for a titanium heating plate, they each play a different role and together achieve an efficient polishing effect. Ammonium sulfate in the polishing liquid mainly plays the role of improving the working environment and improving the escape of nitrogen oxides during polishing, thereby reducing the health hazards to operators.
[0041] 2. In the present application, glucose plays an auxiliary polishing role in the polishing liquid. The addition of glucose helps to obtain a smoother and more uniform polishing surface. Glucose also affects the polishing effect by increasing the viscosity of the polishing liquid or improving the dispersibility of the polishing particles.
[0042] 3. In this application, the polishing liquid temperature, polishing voltage and polishing time are set to ensure uniform polishing. Use running water to rinse to ensure that the surface of the workpiece is clean. Use nitrogen to blow dry the workpiece to avoid residual water stains. Ensure that nitrogen blows evenly to avoid local over-dryness or over-wetness. DETAILED DESCRIPTION
[0043] The present application is further described in detail below in conjunction with embodiments.
[0044] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0045] Preparation example of modified xanthan gum Preparation Example 1-1 The preparation method of modified xanthan gum comprises the following steps: dispersing 10 kg of xanthan gum in 15 L of deionized water, stirring at 75° C. for 1.5 h, adding potassium hydroxide, adjusting the pH value to 11, adding polysorbate and saccharin, stirring at 85° C. for 55 min, filtering, washing with anhydrous ethanol, and drying to obtain modified xanthan gum.
[0046] The mass ratio of xanthan gum, polysorbate and saccharin is 1:0.3:0.8.
[0047] Preparation Example 1-2 The difference from Preparation Example 1-1 is that no polysorbate is added.
[0048] Preparation Example 1-3 The difference from Preparation Example 1-1 is that saccharin is not added.
[0049] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of xanthan gum, polysorbate and saccharin is 1:0.1:0.6.
[0050] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of xanthan gum, polysorbate and saccharin is 1:0.05:1.2.
[0051] Preparation example of modified acrylic resin Preparation Example 2-1 The preparation method of modified acrylic resin comprises the following steps: dispersing 12 kg of methyl methacrylate in 20 L of deionized water, stirring at 65° C. for 2 h, adding cellulose nanocrystals and sodium dodecylbenzene sulfonate, stirring at 130° C. for 3 h, drying, and grinding to obtain modified acrylic resin.
[0052] The mass ratio of methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate is 1:0.4:0.1.
[0053] Preparation Example 2-2 The difference from Preparation Example 2-1 is that no cellulose nanocrystals are added.
[0054] Preparation Example 2-3 The difference from Preparation Example 2-1 is that sodium dodecylbenzenesulfonate is not added.
[0055] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate is 1:0.5:0.2.
[0056] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate is 1:0.1:0.6. Example
[0057] Example 1 A titanium heating plate surface nano-polishing process comprises the following steps: placing a titanium heating plate workpiece with a diameter of 20 cm in a polishing liquid, the polishing liquid temperature is 52° C., electrochemical polishing is performed at a constant voltage, the voltage is controlled at 25 V, the power-on time is 8 minutes, and after the electrochemical polishing is completed, the workpiece is taken out, washed with water, and dried with nitrogen; The polishing liquid includes 5 kg of polishing salt and 100 kg of deionized water. The polishing salt includes the following components in percentage by mass: 35% of ammonium sulfate, 30% of sodium citrate, 10% of glucose and 25% of citric acid.
[0058] During the electrolytic polishing process, the titanium heating plate workpiece is placed in the polishing tank liquid, and the conductive beam is fixed on the movable anode conductive seat; the titanium heating plate workpiece is used as the anode, the stainless steel is used as the cathode, and the distance between the anode and cathode is 5cm. During polishing, a circulating pump is used to stir the electrolyte.
[0059] The preparation method of the polishing liquid comprises the following steps: uniformly mixing ammonium sulfate, sodium citrate, glucose and citric acid, dispersing the mixture in deionized water, and stirring the mixture for 3 hours to obtain the polishing liquid.
[0060] Example 2 A titanium heating plate surface nano-polishing process, which differs from Example 1 in that it comprises the following steps: placing the titanium heating plate workpiece in a polishing liquid, the polishing liquid temperature is 55° C., electrochemical polishing is performed at a constant voltage, the voltage is controlled at 20V, and the power-on time is 10 minutes. After the electrochemical polishing is completed, the workpiece is taken out, washed with water, and dried with nitrogen; The polishing liquid includes 5 kg of polishing salt and 100 kg of deionized water. The polishing salt includes the following components in percentage by mass: 31% of ammonium sulfate, 28% of sodium citrate, 13% of glucose and 28% of citric acid.
[0061] Example 3 A titanium heating plate surface nano-polishing process, which differs from Example 1 in that it comprises the following steps: placing a titanium heating plate workpiece in a polishing liquid, the polishing liquid temperature is 50° C., electrochemical polishing is performed at a constant voltage, the voltage is controlled at 30V, and the power-on time is 5 minutes. After the electrochemical polishing is completed, the workpiece is taken out, washed with water, and dried with nitrogen; The polishing liquid includes 8 kg of polishing salt and 100 kg of deionized water. The polishing salt includes the following components in percentage by mass: 40% of ammonium sulfate, 31% of sodium citrate, 7% of glucose and 22% of citric acid.
[0062] Example 4 A titanium heating plate surface nano-polishing process, which differs from Example 1 in that the workpiece is pre-treated before being placed in the polishing liquid, comprising the following steps: soaking the workpiece in a 100 kg acid solution for 30 minutes, then washing with water, then placing the workpiece in a cleaning liquid for ultrasonic cleaning for 1 hour, washing with ethanol, and drying to obtain a pre-treated workpiece; The cleaning liquid includes the following components by weight: 9kg of sodium hydroxide, 35kg of sodium gluconate, 3kg of sodium borate, 18kg of sodium ethylenediaminetetraacetate, 5kg of modified xanthan gum, 8kg of octylphenol polyoxyethylene ether, 8kg of modified acrylic resin, 2kg of triethanolamine oleic acid soap, 3kg of polydimethylsilane, and 350kg of deionized water.
[0063] The acid solution is sulfuric acid, hydrofluoric acid, and deionized water in a mass ratio of 30:9:100.
[0064] The modified xanthan gum was prepared by using Preparation Example 1-1, and the modified methyl methacrylate was prepared by using Preparation Example 2-1.
[0065] Example 5 A titanium heating plate surface nano-polishing process, which differs from Example 4 in that the workpiece is pre-treated before being placed in the polishing liquid, comprising the following steps: soaking the workpiece in an acid solution for 35 minutes, then washing with water, then ultrasonically cleaning the workpiece in a cleaning solution for 2 hours, cleaning with ethanol, and drying to obtain a pre-treated workpiece; The cleaning liquid includes the following components by weight: 6kg of sodium hydroxide, 30kg of sodium gluconate, 5kg of sodium borate, 15kg of sodium ethylenediaminetetraacetate, 3kg of modified xanthan gum, 5kg of octylphenol polyoxyethylene ether, 6kg of modified acrylic resin, 5kg of triethanolamine oleic acid soap, 1kg of polydimethylsilane, and 380kg of deionized water.
[0066] The acid solution is sulfuric acid, hydrofluoric acid, and deionized water in a mass ratio of 35:6:100.
[0067] Example 6 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 4 in that the modified xanthan gum is prepared using Preparation Example 1-2.
[0068] Example 7 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 1 in that the modified xanthan gum is prepared using Preparation Examples 1-3.
[0069] Example 8 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 1 in that the modified xanthan gum is prepared using Preparation Examples 1-4.
[0070] Example 9 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 1 in that the modified xanthan gum is prepared using Preparation Examples 1-5.
[0071] Example 10 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 1 in that the modified methyl methacrylate is prepared using Preparation Example 2-2.
[0072] Embodiment 11 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 1 in that the modified methyl methacrylate is prepared using Preparation Example 2-3.
[0073] Example 12 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 1 in that the modified methyl methacrylate is prepared using Preparation Examples 2-4.
[0074] Example 13 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 1 in that the modified methyl methacrylate is prepared using Preparation Examples 2-5.
[0075] Comparative Example Comparative Example 1 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 1 in that ammonium sulfate is not added.
[0076] Comparative Example 2 A nano-polishing process for the surface of a titanium heating plate, which differs from Example 1 in that no glucose is added.
[0077] Performance testing The high-efficiency heat-resistant and scald-proof paper cups prepared in Examples 1-13 and Comparative Examples 1-2 were subjected to performance tests; Glossiness: The glossiness of the surface of each polished steel plate was tested using a micro gloss meter A-4430 (BYK, Germany).
[0078] Workpiece appearance: Observe the surface of each workpiece with the naked eye. If the workpiece surface appearance is uniform, without different colors and snowflakes, it is 8-10 points; if the workpiece surface appearance is uniform, with slight color difference and slight snowflakes, it is 6-8 points; if the workpiece surface appearance is uniform, with partial color difference and partial snowflakes, it is 4-6 points; if the workpiece surface appearance is uneven, with large color difference and large snowflakes, it is 0-4 points.
[0079] Roughness: Tested using a surface roughness tester.
[0080] Stability: The percentage of the workpiece surface that can remain smooth and spot-free after being placed for 48 hours. The test results are shown in Table 1.
[0081] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, the titanium heating plate obtained by the titanium heating plate surface nano-polishing process in Examples 1-3 of the present application has better comprehensive performance, among which, the glossiness of Example 1 is 57gu, the appearance score is 8.2 points, the roughness Ra is 0.356μm, and the stability performance is 88%. It shows that the polishing liquid prepared in the present application has a good polishing effect. When ammonium sulfate, sodium citrate, glucose and citric acid are mixed as the titanium heating plate polishing liquid, each plays a different role and jointly achieves an efficient polishing effect.
[0082] Comparative Examples 1-2 do not add ammonium sulfate and glucose, respectively. As can be seen from Table 1, the test results of gloss, appearance score, roughness, and stability performance are significantly worse than those of Examples 1-3, indicating that ammonium sulfate has good electrochemical properties and polishing effects, helps to adjust the pH value of the polishing liquid, stabilizes the polishing process, and improves the surface gloss and flatness of the workpiece after polishing. The addition of glucose helps to obtain a smoother and more uniform polished surface, and affects the polishing effect by increasing the viscosity of the polishing liquid or improving the dispersibility of the polishing particles.
[0083] In Example 4-5, the workpiece is pretreated before being placed in the polishing liquid. As can be seen from Table 1, the test results of glossiness, appearance score, roughness, and stability performance are significantly improved, among which, the glossiness of Example 4 is 68gu, the appearance score is 9.6 points, the roughness Ra is 0.231μm, and the stability performance is 98%. This shows that the pretreated workpiece further cleans the surface of the titanium heating plate, and the combination of each component has a synergistic effect, maintaining the stability and cleaning effect of the cleaning liquid.
[0084] The preparation method of modified xanthan gum of embodiment 6-7 does not add polysorbate and saccharin respectively, and the mass ratio of xanthan gum, polysorbate and saccharin is changed in embodiment 8-9. As can be seen from Table 1, the glossiness, appearance score, roughness and stability performance test effect of embodiment 6-7 are obviously worse than those of embodiment 4-5, and the corresponding performance test effect of embodiment 9 is better than that of embodiment 6-7, but worse than that of embodiment 4-5 and embodiment 8, indicating that polysorbate has excellent wetting, dispersion and emulsification properties, can stabilize the colloidal structure in the alkaline solution of xanthan gum, and prevent the aggregation and precipitation of colloidal particles. Saccharin can form a tighter network structure with xanthan gum, thereby increasing the viscosity of the system. There is a synergistic effect between xanthan gum, polysorbate and saccharin, which is subsequently applied to the surface cleaning of titanium heating plate. The wetting and dispersion of polysorbate are combined with the suspension of xanthan gum, which can more effectively remove the stains and dirt on the surface of titanium heating plate.
[0085] The preparation method of modified acrylic resin in Examples 10-11 does not add cellulose nanocrystals and sodium dodecylbenzene sulfonate respectively, and Examples 12-13 change the mass ratio of methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate. As can be seen from Table 1, the glossiness, appearance score, roughness and stability test results of Examples 10-11 are significantly worse than those of Examples 4-5, and the corresponding performance test results of Example 13 are better than those of Examples 10-11, but worse than those of Examples 4-5 and Example 12, indicating that the mixture of methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate has a synergistic effect, and methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate can form a cross-linked network structure to improve the mechanical properties, weather resistance, adhesion and stability of acrylic resin. Applied to the surface of titanium heating plate, methyl methacrylate, cellulose nanocrystals and sodium dodecylbenzene sulfonate cooperate with each other and play a cleaning role together, which not only improves the cleaning efficiency, but also reduces the risk of damage to the surface of titanium heating plate.
[0086] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A titanium heating plate surface nano-polishing process, characterized in that: The method comprises the following steps: placing the workpiece in a polishing liquid, the temperature of the polishing liquid is 50-55°C, electrochemical polishing is performed at a constant voltage, the voltage is controlled at 20-30V, and the power-on time is 5-10min. After the electrochemical polishing is completed, the workpiece is taken out, washed with water, and dried with nitrogen; The polishing liquid comprises polishing salt and deionized water, wherein the polishing salt comprises the following components in percentage by mass: 30-40% ammonium sulfate, 28-32% sodium citrate, 7-13% glucose and 22-28% citric acid.
2. The nano-polishing process for the surface of a titanium heating plate according to claim 1, characterized in that: The polishing salt comprises the following components in percentage by mass: 35% ammonium sulfate, 30% sodium citrate, 10% glucose and 25% citric acid.
3. The nano-polishing process for the surface of a titanium heating plate according to claim 1, characterized in that: The workpiece is pretreated before being placed in the polishing liquid, comprising the following steps: soaking the workpiece in an acid solution for 30-35 minutes, then washing with water, then placing the workpiece in a cleaning solution for ultrasonic cleaning for 1-2 hours, washing with ethanol, and drying to obtain a pretreated workpiece; The cleaning solution comprises the following components: sodium hydroxide, sodium gluconate, sodium borate, sodium ethylenediaminetetraacetate, modified xanthan gum, octylphenol polyoxyethylene ether, modified acrylic resin, triethanolamine oleic acid soap, polydimethylsilane and deionized water.
4. The nano-polishing process for the surface of a titanium heating plate according to claim 3, characterized in that: The cleaning solution comprises the following components in parts by weight: 6-9 parts of sodium hydroxide, 30-35 parts of sodium gluconate, 3-5 parts of sodium borate, 15-18 parts of sodium ethylenediaminetetraacetate, 3-5 parts of modified xanthan gum, 5-8 parts of octylphenol polyoxyethylene ether, 6-8 parts of modified acrylic resin, 2-5 parts of triethanolamine oleic acid soap, 1-3 parts of polydimethylsilane, and 350-380 parts of deionized water.
5. The nano-polishing process for the surface of a titanium heating plate according to claim 3, characterized in that: The preparation method of the modified xanthan gum comprises the following steps: dispersing the xanthan gum in deionized water, stirring at 70-75°C for 1-2h, adding potassium hydroxide, adjusting the pH value to 10-11, adding polysorbate and saccharin, stirring at 80-85°C for 50-55min, filtering, washing with anhydrous ethanol, and drying to obtain the modified xanthan gum.
6. The nano-polishing process for the surface of a titanium heating plate according to claim 5, characterized in that: The mass ratio of the xanthan gum, polysorbate and saccharin is 1:0.1-0.3:0.6-0.
8.
7. The nano-polishing process for the surface of a titanium heating plate according to claim 3, characterized in that: The preparation method of the modified acrylic resin comprises the following steps: dispersing methyl methacrylate in deionized water, stirring at a temperature of 60-65° C. for 1-2 hours, adding cellulose nanocrystals and sodium dodecylbenzene sulfonate, stirring at a temperature of 120-130° C. for 2-3 hours, drying, and grinding to obtain the modified acrylic resin.
8. The nano-polishing process for the surface of a titanium heating plate according to claim 7, characterized in that: The mass ratio of the methyl methacrylate, the cellulose nanocrystals and the sodium dodecylbenzene sulfonate is 1:0.4-0.5:0.1-0.
2.
9. The nano-polishing process for the surface of a titanium heating plate according to claim 3, characterized in that: The acid solution is sulfuric acid, hydrofluoric acid and deionized water in a mass ratio of 30-35:6-9:
100.
10. The nano-polishing process for the surface of a titanium heating plate according to claim 1, characterized in that: The method for preparing the polishing liquid comprises the following steps: uniformly mixing ammonium sulfate, sodium citrate, glucose and citric acid, dispersing the mixture in deionized water, and stirring the mixture for 2-3 hours to obtain the polishing liquid.
Citation Information
Patent Citations
Metal piece and method for processing surface of metal piece
CN101591798A
Treatment method of titanium-aluminum composite part, preparation method of combination of titanium-aluminum composite part and resin and product
CN114606560A
Liquid-phase plasma nano-polishing solution of kovar alloy 4j29 and preparation method and application of liquid-phase plasma nano-polishing solution
CN115449891A
Plasma polishing process for silver ornaments
CN118390146A
Metallization utilizing a catalyst which is removed or deactivated from undesired surface areas
US4749449A
Cited By
Stainless steel electrolytic polishing solution suitable for EBSD sample preparation and operation conditions of stainless steel electrolytic polishing solution
CN120465091A